Blood-based biomarkers suggest prolonged axonal Injury following pediatric mild traumatic brain injury - Andrew R. Mayer; Tracey V. Wick; Jessica R. McQuaid; Masen L. Boucher; Andrew B. Dodd; Cidney R. Robertson-Benta; Harm J. van der Horn; Erik B. Erhardt; Robert E. Sapien; Rawan Tarawneh; Rebekah Mannix (Scientific Reports)
Abstract Pediatric mild traumatic brain injury (pmTBI) affects millions of youth annually but underlying pathophysiology and time for physiological recovery remains unknown. Non-fasting plasma samples were obtained in 59 pmTBI (28 females; age 14.9 ± 2.7) at approximately 7 days and 4 months post-injury and in 41 matched healthy controls (HC: 20 females; age 14.3 ± 2.8). Samples were analyzed for GFAP, NFL, Tau, pTau181 and UCH-L1 protein concentrations in conjunction with a clinical battery. Significant effects of diagnosis (pmTBI > HC) existed at ~ 7 days (p < 0.001; Cohen’s d = 0.72) and ~ 4 months (p = 0.015; Cohen’s d = 0.41) post-injury for NFL. NFL was also elevated in pmTBI with significant alterations to mental status (e.g., post-traumatic amnesia) relative to patients without (p = 0.014; Cohen’s d = 0.77). UCH-L1, GFAP and pTau181 did not differ between groups, but demonstrated negative associations with days post-injury (small to medium effect sizes) suggestive of a more rapid release/clearance. Post-concussive symptoms had the best diagnostic classification accuracy at ~ 7 days, but NFL ranked higher at 4 months post-injury. Preliminary findings highlight dynamic fluctuations in blood-based biomarkers in the first week of pmTBI, with ongoing evidence of protein release (NFL) at 4 months. NFL demonstrated additional promise for delineating injury severity within the spectrum of pmTBI.